2003
DOI: 10.1159/000075525
|View full text |Cite
|
Sign up to set email alerts
|

LOS Function and Obesity: The Impact of Untreated Obesity, Weight Loss, and Chronic Gastric Balloon Distension

Abstract: Background/Aims: In obesity, many gastro-oesophageal reflux promoting factors are present. Weight reduction is advised to symptomatic overweight subjects. The aim of the present study was to investigate the influences of untreated obesity, weight loss, and chronic gastric balloon distension on the lower oesophageal sphincter (LOS) function. Methods: Patients entering a randomized, double-blind, sham-controlled study of balloon treatment, consisting of 4 months of either sham balloon or balloon treatment follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 17 publications
2
20
1
4
Order By: Relevance
“…Therefore we agree with authors who affirm that for obese patients suffering from GERD weight loss in conjunction with antisecretory medications is first-line therapy [49]. Indeed, evidence supports the role of weight loss as a beneficial therapy for reflux symptoms [50, 51]. When medical efforts to lose weight fail, bariatric surgical procedure are considered (laparoscopic adjustable gastric band; vertical banded gastroplasty; Roux-en-y gastric bypass) [51, 52].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore we agree with authors who affirm that for obese patients suffering from GERD weight loss in conjunction with antisecretory medications is first-line therapy [49]. Indeed, evidence supports the role of weight loss as a beneficial therapy for reflux symptoms [50, 51]. When medical efforts to lose weight fail, bariatric surgical procedure are considered (laparoscopic adjustable gastric band; vertical banded gastroplasty; Roux-en-y gastric bypass) [51, 52].…”
Section: Discussionsupporting
confidence: 85%
“…37–39 In the first RCT, including 17 patients, 3 of 5 patients with pathological pH-measurements got normalized pH-measurements with weight loss of 31.3–44.0 kg after 4 months. 37 In the second RCT, 23 patients with a mean weight loss of 11.2 kg within 13 weeks had decreased time with esophageal pH <4 (from 5.60% to 3.72%, P <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…38 These results were supported by the third RCT of 17 sham treated patients, where mean weight loss of 12.5 kg within 13 weeks improved time with upright pH <4 (from 8.0% to 5.5%, P <0.05). 39 …”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported adverse event data for subjects randomized to the sham arm, followed by cross-over to treatment 1318 . In partial cross-over design studies, the estimated average pooled increased risk of developing a non-severe event after being randomized to the sham arm was risk ratio = 1.33 (95% CI, 1.14 – 1.56), p<0.001, I-squared = 6.74, Tau-squared = 0.003, compared with those randomized to the treatment group.…”
Section: Resultsmentioning
confidence: 99%